PENGEMBANGAN TES KETERAMPILAN PROSES SAINS DASAR SD/MI - Widayanti, Esti Yuli (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2016)
The purpose of this study is to develop an valid and reliable test to measure the student’s basic science process skills in elementary school. This is a Research and Development (R&D) study, the research methods used to produce a specific product and test it’s effectiveness. To achieve the objectives, the research carried out in two phases, namely the phase of the instrument development process and psychometric analysis phase. The first phase includes: identifying an objective test; specifying the content/content of tests or describe the science process skill that will be tested; arrange grating instruments including indicators of there spective skills and items per indicator; write the item / items according tothe indicators; and perform expert judgment (to convince the face and content validity). The second phase is a psychometric analysis conducted by placing a pilot test. Results of the study are (1). Conduct the first phase of the development of the test, the result is the compilation of 24 multiple-choice items that have been valid after various appropriate revisions by expert advice.(2) conduct the second phase of the test development which is a psychometric analysis by conducting pilot tests to determine the internal reliability while recognizing the difficulty and discrimination level. Items accepted are those that have a level of difficulty, different power, distribution of answers suited to the ideal criteria. The results of this study phase are 10 items test are accepted as good items (item number 1, 2, 7, 8, 9, 15, 17, 18, 22 and 23), 13 items were fixed/revised (item number 3, 4, 5, 6 , 11, 12, 13, 14, 16, 19, 20, 21, 24), and the first question thrown away/not in use (number 10). Level reliability test items is fair (0,524).)Keywords: Test Development, Skill Process, Elementary Science